Real-world efficacy and safety of pyrotinib in patients with HER2-positive metastatic breast cancer: A prospective real-world study - Zhang, Qiongwen; He, Ping; Tian, Tinglun; Yan, Xi; Huang, Juan; Zhang, Zhang; Zheng, Hong; Zhong, Xiaorong; Luo, Ting (Frontiers in Pharmacology, 2023)
Background Pyrotinib, a novel irreversible EGFR/HER2 dual tyrosine kinase inhibitor, shows encouraging anticancer activity and acceptable tolerability in multiple phase II and phase III randomized clinical trials, but the real-world data of pyrotinib, especially the outcomes in HER2-positive metastatic breast cancer, have been rarely reported. Here, we evaluated the treatment outcomes of pyrotinib in real-world practice in patients with HER2-positive metastatic breast cancer (MBC). Methods This was a prospective, real-world, observational cohort study. Through the Breast Cancer Information Management System, HER-2 positive MBC patients treated with pyrotinib between 2017/06 and 2020/09 were included. Provider-reported objective response rate, progression-free survival (PFS), and overall survival (OS) were considered in the assessment of treatment outcomes. Tumor responses to pyrotinib treatment were calculated using RECIST 1.1. Adverse events were evaluated using clinical records. Results The trial involved 113 individuals who were receiving pyrotinib treatment, with an average age of 51 years. Complete response, partial response and stable disease were observed in 9 (8.0%), 66 (58.4%), and 17 (15.0%) patients, respectively, while progressive disease was recorded in 20 (17.7%) patients. After a median follow-up of 17.2 months, the median PFS was 14.1. The most common adverse events of any grade were diarrhea (87.6%), vomiting (31.9%), and palmar-plantar erythrodysesthesia (26.6%). Among the patients with brain metastases, the median PFS and OS were 15.2 and 19.8 months, respectively. In addition, pyrotinib has similar efficacy in various subtypes of HER2-positive MBC patients, as shown by the lack of a significant difference of PFS and OS among pyrotinib-treated patients with or without brain metastases, or patients using pyrotinib as first-line, second-line, third-line or beyond therapies. Conclusions Our real-world results demonstrated equivalent clinical efficacy in HER-2 positive MBC patients compared to phase II and phase III clinical trials with pyrotinib, and promising outcomes in patients with brain metastases.